Activity and Stability of Ruddlesden-Popper-Type Lan+1NinO3n+1 (n=1, 2, 3, and 8) Electrocatalysts for Oxygen Reduction and Evolution Reactions in Alkaline Media - Yu, J.; Sunarso, J.; Zhu, Y.; Xu, X.; Ran, R.; Zhou, W.; Shao, Zongping (2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Increasing energy demands have stimulated intense research activity on cleaner energy conversion such as regenerative fuel cells and reversible metal-air batteries. It is highly challenging but desirable to develop low-cost bifunctional catalysts for both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER), the lack of which is currently one of the major limiting components towards commercialization of these technologies. Here, we have conducted a systematic study on the OER and ORR performances of the Ruddlesden-Popper family of Lan+1NinO3n+1 (n=1, 2, 3, and 8) in an alkaline medium for the first time. It is apparent that the Ni-O bond lengths and the hyperstoichiometric oxides in the rock-salt layers correlate with the ORR activities, whereas the OER activities appear to be influenced by the OH- content on the surface of the compounds. In our case, the electronic configuration fails to predict the electrocatalytic activity of these compounds. This work provides guidelines to develop new electrocatalysts with improved performances.